ANALISIS MAKNA DENOTATIF, KONOTATIF DAN MITOS PADA KONTEN TIKTOK @ABIR.SAG: SEMIOTIKA ROLAND BARTHES - Aisyah Nabilah Azhaar; Afiyah Salma Az-Zahro; Aura Kholifatunnisa; Munif Muhammad Hatim (2025)
This study aims to analyze the denotative, connotative and mythological meanings in TikTok content by creator Abir Shagir through Roland Barthes’ semiotic framework. The research is grounded in the growing use of social media, particularly TikTok, as a medium for representing culture and identity through culinary content. This qualitative research employs a descriptive approach, collecting data through observation and note-taking on three selected videos showcasing Middle Eastern culinary practices. The analysis focuses on visual signs such as traditional clothing, national flags, keffiyeh, and food-sharing practices, interpreted within Barthes’ three levels of meaning: denotation, connotation, and myth. The findings reveal that Abir Shagir’s content constructs ideological meanings representing cultural identity, cross-national solidarity, and generosity values. At the myth level, culinary practices transform into instruments of cultural diplomacy and ideological reproduction, affirming the applicability of Barthes’ theory in analyzing visual and symbolic strategies in contemporary digital media. The study concludes that culinary content on social media is not merely a cooking activity but serves as a strategic medium for cultural and political communication.